2021
DOI: 10.1186/s12885-021-07841-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of preoperative D-dimer, fibrinogen and platelet levels in patients with oral squamous cell carcinoma

Abstract: Background The relationship between cancer and coagulation has been intensively studied in recent years; however, the effects of coagulation factors on oral squamous cell carcinoma (OSCC) have rarely been reported. This study aimed to investigate the relationship between preoperative D-dimer (DD), fibrinogen (FIB), platelets (PLT) and OSCC, as well as the prognostic value of DD, FIB and PLT in OSCC. Methods We retrospectively investigated a total o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
(21 reference statements)
2
16
0
1
Order By: Relevance
“…However, most of these individualized medical treatments based on gene detection are invasive and expensive and cannot fully define the spatial heterogeneity of tumors. Numerous studies have demonstrated that hematological parameters have great potential in tumor prognostic stratification (7,9,(19)(20)(21); unlike genetic markers, hematological parameters obtained from preoperative peripheral blood tests have the advantages of non-invasiveness, low cost, and easy access. Previous studies have demonstrated that high preoperative levels of NLR and FIB and low levels of LMR are associated with adverse clinical outcomes of AM (7,11,22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of these individualized medical treatments based on gene detection are invasive and expensive and cannot fully define the spatial heterogeneity of tumors. Numerous studies have demonstrated that hematological parameters have great potential in tumor prognostic stratification (7,9,(19)(20)(21); unlike genetic markers, hematological parameters obtained from preoperative peripheral blood tests have the advantages of non-invasiveness, low cost, and easy access. Previous studies have demonstrated that high preoperative levels of NLR and FIB and low levels of LMR are associated with adverse clinical outcomes of AM (7,11,22).…”
Section: Discussionmentioning
confidence: 99%
“…The coagulation system is an integral component of the unique vascular microenvironment for tumor proliferation and progress ( 28 , 29 ). FIB and DD, as important factors in the coagulation cascade and fibrinolysis processes, respectively, have been shown to be involved in the invasive process of a variety of malignancies ( 8 , 19 , 30 ). The “net” constructed by FIB in the extracellular matrix promotes cell adhesion and tumor invasion ( 30 ); in addition, FIB ultimately promotes angiogenesis and tumor growth by binding to growth factors such as vascular endothelial growth factor and fibroblast growth factor-2 ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of CTC represents an independent risk factor of recurrence and clotting may be a protective mechanism for these cells, ensuring their perioperative dissemination. Recent studies showing the prognostic value of biomarkers of hemostasis in surgical OSCC [ 32 , 33 ] open the interesting possibility of better and more personalized anticoagulation strategies during the perioperative period.…”
Section: Key Perioperative Events and The Relevant Biological Parametersmentioning
confidence: 99%
“…[19][20][21][22] During tumor progression, due to metastasis, infiltration and destruction of malignant cells, abundant pro-coagulant substances are released into the blood, leading to hypercoagulable state. [23][24][25] Ji et al reported that high plasma fibrinogen levels were significantly related to poor prognosis of cases with gastrointestinal malignant tumor. 22 Nevertheless, the correlation between FIB (fibrinogen) and prognosis in unresectable HCC patients treated with lenvatinib and PD-1 (programmed cell death receptor-1) remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%